Probable maximum precipitation (PMP) over mountainous region of cameron highlands-batang padang catchment of Malaysia - Sidek L.M.; Nor M.D.M.; Rakhecha P.R.; Basri H.; Jayothisa W.; Muda R.S.; Ahmad M.N.; Razad A.Z.A. (Institute of Physics Publishing, 2023)
The Cameron Highland Batang Padang (CHBP) catchment situated on the main mountain range of Peninsular Malaysia is of large economical importance where currently a series of three dams (Sultan Abu Bakar, Jor and Mahang) exist in the development of water resources and hydropower. The prediction of the design storm rainfall values for different return periods including PMP values can be useful to review the adequacy of the current spillway capacities of these dams. In this paper estimates of the design storm rainfalls for various return periods and also the PMP values for rainfall stations in the CHBP catchment have been computed for the three different durations of 1, 3 & 5 days. The maximum values for 1 day, 3 days and 5 days PMP values are found to be 730.08mm, 966.17mm and 969.0mm respectively at Station number 4513033 Gunung Brinchang. The PMP values obtained were compared with previous study results undertaken by NAHRIM. However, the highest ratio of 1 day, 3 day and 5 day PMP to highest observed rainfall are found to be 2.30, 1.94 and 1.82 respectively. This shows that the ratio tend to decrease as the duration increase. Finally, the temporal pattern for 1 day, 3day and 5 days have been developed based on observed extreme rainfall at station 4513033 Gunung Brinchang for the generation of Probable Maximum Flood (PMF) in dam break analysis. Published under licence by IOP Publishing Ltd.